Genetic similarity and phenotypic diversity of commensal and pathogenic strains of Candida albicans isolated from the oral cavity. - Hellstein, J (1993)
Colony phenotype and genetic similarity were assessed within and between groups of commensal and pathogenic strains of Candida albicans collected from the oral cavities of individuals in a single geographical locale. Thirty-eight percent of pathogenic isolates contained predominant or minor variant colony morphologies (other than smooth) when samples from the sites of infection were cultured on plates, while 16% of commensal isolates contained minor variant colony morphologies when samples from the sites of carriage were cultured. The genetic similarities of isolates within and between groups were assessed by DNA fingerprinting by using Southern blot hybridization with the fingerprinting probe Ca3 and analysis with the computer-assisted, automated Dendron system. Both the commensal and the pathogenic groups contained a major cluster of genetically similar C. albicans isolates representing 31 and 33% of the strains in the respective groups. When a combined dendrogram of both commensal and pathogenic isolates was generated, the major clusters of genetically similar isolates in each group mixed into one large cluster. Minor clusters in the individual dendrograms also mixed. These results suggest common clonal origins for commensal and pathogenic strains in the same geographical locale.